Stimulasi Sensorimotor Sebagai Layanan Holistik Integratif Unggulan di PAUD Terpadu Zaki's Club Gemolong Kabupaten Sragen - Rahayu, Sri (2016)
The period of 5 (five) years of the life of the child is a 'golden period' (the golden period) or 'Window Opportunities' (window of opportunity) in laying the foundations of child development. The quality of child development during this period will determine the quality of physical, mental, emotional, social, learning and behavior throughout his life. Therefore, this golden period should be utilized (worked) as well as possible to optimize the development of the child, one with sensorimotor stimulation. Sensorimotor stimulation is a touch stimulation throughout the body associated with the sensory and body movements. The purpose of this study were (1) To describe the implementation of sensorimotor stimulation in early childhood Integrated Zaki's Club Gemolong. (2) To determine the suitability of sensorimotor stimulation in early childhood implementation of Integrated Zaki's Club with theory. This research was conducted at Integrated early childhood Zaki's Club Gemolong for 16 weeks. This research is a qualitative descriptive study with case study. Subjects were sensorimotor stimulation and objects of research are educators, learners and parents of early childhood learners Integrated Zaki's Club Gemolong. Sources of data taken by purposive sampling that is by researchers chose informants considered knowledgeable and trustworthy to be a source of data. Data analysis techniques used are participant observation is the analysis that integrates with the entire research process. Conclusion The results of this study were (1) sensorimotor stimulation is stimulation of touch on the entire body of a child who follow the pattern of human growth and development by: (a) touches the head; (B) touches the introduction of body joints; (C) touches the introduction of body axis; (D) touches the back; (E) touches the body unification. (2) Imlpelentasi sensorimotor stimulation compatible with the theory that a touch direction after the direction of growth and human perkembanan, and in the near future could be seen the impact, namely: (a) Acceleration of time on child attachment relationship with educators; (B) Increasing the intensity and quality of the child's bedroom.